2002
DOI: 10.1023/a:1021980019452
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Examples of reverse turns as recognition motifs in biological systems can be found in high-resolution crystal structures of antibody-peptide complexes. Development of peptidomimetics is often based on replacing the amide backbone of peptides by sugar rings, steroids, benzodiazepines, or other hetero- and carbocycles. In this approach, the chemical scaffold of the peptide backbone can be replaced while retaining activity as long as the pharmacophoric groups of the peptide side chains stay in relatively the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…D-Glucose, L-glucose and L-mannose structural isomers were synthesized and displayed different subtype selectivity for somatostatin receptors [149]. Marshall and his co-workers [150] showed that metal complexes of chiral pentaazacrowns (MAC), derived by reduction of cyclic pentapeptides, fixed side chains in orientations comparable to those of ideal b-turns. The minor changes in side chain orientation with different metals offer an opportunity for subtle optimization of binding specificity not available through conventional organic chemistry.…”
Section: Mimics Of Turn Surface and Functionmentioning
confidence: 99%
“…D-Glucose, L-glucose and L-mannose structural isomers were synthesized and displayed different subtype selectivity for somatostatin receptors [149]. Marshall and his co-workers [150] showed that metal complexes of chiral pentaazacrowns (MAC), derived by reduction of cyclic pentapeptides, fixed side chains in orientations comparable to those of ideal b-turns. The minor changes in side chain orientation with different metals offer an opportunity for subtle optimization of binding specificity not available through conventional organic chemistry.…”
Section: Mimics Of Turn Surface and Functionmentioning
confidence: 99%
“…In contrast to many polyoxometallates, this cluster has been demonstrated to be stable under physiological conditions. Marshall and coworkers proposed the utilization of metal complexes of chiral azacrowns (MACs) as a strategy to influence the conformation of these macrocycles and to fix the chiral side chains in orientations comparable with those of peptidic b-turns [18][19][20]. For example, the MAC complex 3 was proposed to serve as a nonpeptidic inhibitor of amylase by mimicking the active reversed b-turn sequence Trp18-Arg19-Tyr20 of the proteinaceous amylase inhibitor tendamistat (Fig.…”
Section: Metal Complexes As Structural Scaffoldsmentioning
confidence: 99%
“…[6][7][8]11 Two methods used to nucleate reverse-turn structures incorporate a sequence of either pro-Pro or Pro-pro at the i+1 and i+2 positions [12][13][14] of the turn, or use small cyclic peptides either cyclized through side chains or head-totail. 5,7,15,16 Cyclic peptides are widely investigated for therapeutic use due to their rigid scaffold and bioavailability. 17 Cyclic peptides, such as h-Defensins, naturally occur in many organisms and have a broad range of activity, acting as antibiotics or antivirals for HIV-1, herpes simplex, or influenza A viruses.…”
Section: Introductionmentioning
confidence: 99%